Public-private partnership to rapidly strengthen and scale COVID-19 response in Western Kenya - van Duijn, Shannen; Barsosio, Hellen C.; Omollo, Mevis; Milimo, Emmanuel; Akoth, Isdorah; Aroka, Robert; de Sanctis, Teresa; K'Oloo, Alloys; June, Micah J.; Houben, Nathalie; Wilming, Charlotte; Otieno, Kephas; et al. (Frontiers in Public Health, 2023)
INTRODUCTION: In Africa almost half of healthcare services are delivered through private sector providers. These are often underused in national public health responses. To support and accelerate the public sector’s COVID-19 response, we facilitated recruitment of additional private sector capacity by initiating a public-private partnership (PPP) in Kisumu County, Kenya. In this manuscript we demonstrate this PPP's performance. METHODS: COVID-19 diagnostic testing formed the basis for a PPP between Kenyan Medical Research Institute (KEMRI), Department of Health Kisumu County, PharmAccess Foundation, and local faith-based and private healthcare facilities: COVID-Dx. First phase COVID-Dx was implemented from June 01, 2020, to March 31, 2021 in Kisumu County, Kenya. Trained laboratory technologists in participating healthcare facilities collected nasopharyngeal and oropharyngeal samples from patients meeting the Kenyan MoH COVID-19 case definition. Healthcare workers in participating facilities collected patient clinical data using a digitized MoH COVID-19 Case Identification Form. We shared aggregated results from these data via (semi-) live dashboards with all relevant stakeholders through their mobile phones and tablets. Statistical analyses were performed using Stata 16 to inform project processes. RESULTS: Nine private facilities participated in the project. A patient trajectory was developed from case identification to result reporting, all steps supported by a semi-real time digital dashboard. A total of 4,324 PCR tests for SARS-CoV-2 were added to the public response, identifying 425 positives, accounting for 16% of all COVID-19 tests performed in the County over the given time-period. Geo-mapped and time-tagged information on incident cases was depicted on Google maps through PowerBI-dashboards and fed back to policymakers for informed rapid decision making. Preferential COVID-19 testing was performed on health workers at risk, with 1,009 tests performed (up to 43% of all County health workforce). CONCLUSION: We demonstrate feasibility of rapidly increasing the public health sector COVID-19 response through coordinated private sector efforts in an African setting. Our PPP intervention in Kisumu, Kenya was based on a joint testing strategy and demonstrated that semi-real time digitalization of patient trajectories can gain significant efficiencies, linking public and private healthcare efforts, increasing transparency, support better quality health services and informing policy makers to target interventions.